2017
DOI: 10.3748/wjg.v23.i31.5692
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic domain of tissue factor promotes liver fibrosis in mice

Abstract: AIMTo evaluate the role of tissue factor (TF) and protease activated receptor (PAR)-2 in liver fibrosis.METHODSUsing CCl4 administration for eight weeks, we induced hepatic fibrosis in wild-type C57BL/6 mice and in mice with deletion of the cytoplasmic signalling domain of TF (TF§CT/§CT), deletion of PAR-2 (PAR-2-/-) and combined deletion of TF signalling domain and PAR-2 (TF§CT/§CT/PAR-2-/-). Hepatic fibrosis area was assessed by quantitative imaging of picrosirius red staining. Hepatic collagen content was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
3
12
1
Order By: Relevance
“…This increase was prevented in mice lacking in TF. However, this anti-coagulant phenotype was not associated with a significant reduction of fibrosis [ 37 ], in contrast to other studies [ 30 ].…”
Section: Coagulation In Fibrosis and Disease Progressioncontrasting
confidence: 71%
See 2 more Smart Citations
“…This increase was prevented in mice lacking in TF. However, this anti-coagulant phenotype was not associated with a significant reduction of fibrosis [ 37 ], in contrast to other studies [ 30 ].…”
Section: Coagulation In Fibrosis and Disease Progressioncontrasting
confidence: 71%
“…In line with this theory, experimental inhibition of PARs prevents the fibrogenic response of HSCs and the progression of fibrosis as demonstrated in pre-clinical studies with animal models of liver disease and cell cultures [ 26 , 28 ]. In addition to PAR-1, PAR-2 showed similar pro-fibrotic effects by inducing HSC contraction, collagen production and MMP-2 expression, this last promoting liver fibrosis due to extracellular matrix remodeling [ 25 , 29 , 30 , 31 ]. Furthermore, studies with PAR −/− transgenic mice confirmed the importance of this receptor in several models of liver fibrosis (xenobiotics, carbon-tetrachloride, CCL 4 , and thioacetamide, TAA) [ 30 , 32 , 33 ] and, recently, even in a model fatty liver disease [ 34 ].…”
Section: Coagulation In Fibrosis and Disease Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, all 7 genes that were classified as synergistic were YAP/TAZ targets (Fig 1F, S2 Table) and 9/13 of the genes classified as additive (Fig 1F, S2 Table) were also shown to be regulated by YAP/TAZ [13,[46][47][48][49][50]. Among these genes, CTGF [51,52], IL11 [53], EDN1 [54], SERPINE1/PAI-1 [55], F3/tissue factor [56], CYR61 [57], KLF10 [58], ATF3 [59], FZD8/Frizzled-8 [59] and RUNX1 [60] have been shown to be important profibrotic mediators. Gene expression profiles of these genes are shown in Fig 1G. These results suggested that LPA and TGFβ1 signalling converges on YAP/TAZ and that YAP/TAZ could represent a central node to regulate fibrotic responses.…”
Section: Whole Genome Expression Analysis Reveals Lpa-tgfβ1 Synergy Imentioning
confidence: 96%
“…Since hydroxyproline is a basic constituent of collagen structure, its content can serve as indicator of collagen synthesis (23). Hydroxyproline analysis was performed to assess the amount of collagen in liver tissues (24). In brief, the samples were hydrolyzed with 6 M HCl at 130˚C for 12 h. Then, 1 ml hydroxyproline developer (β-dimethylaminobenzaldehyde solution) was added to the samples and standards.…”
Section: Rat Models Of Liver Fibrosis and Treatment Protocolmentioning
confidence: 99%